Polio vaccine misinformation on social media: turning point in the fight against polio eradication in Pakistan - Muhammad Ittefaq; Mauryne Abwao; Shanawer Rafique (Taylor & Francis Group, 2021)
Pakistan's polio eradication program faces immense challenges, including misinformation on social media that resulted in an increased number of new polio cases in 2019, when viral misleading videos were shared online. In recent years, misinformation has played a critical role in shifting the public's attitude on polio vaccination acceptance in Pakistan. Vaccine misinformation on social media marked a turning point in information consumption habits of Pakistanis and the content moderation policies of social media platforms, as well as the relationship between the government of Pakistan and tech giants like Facebook, Google, and Twitter. This commentary suggests that instead of relying on national-level information, Pakistan's provincial and local health departments should engage with local users on social media to correct vaccine misinformation about polio. Further, vaccine communication must acknowledge the existing information gaps, and take into account readers' and viewers' concerns. To mitigate the amount and spread of visual content related to vaccine misinformation, monitoring visual misinformation more closely, perhaps using the AI capabilities of Google's DeepMind, would be helpful.